Novel non-cooperative power control game algorithm for cognitive radio - Zhao, Jun-Hui; Yang, Tao; Zhang, Xue-Xue (Tongxin Xuebao, 2012)
A novel non-cooperative power control algorithm based on new pricing function and the characteristics of cognitive radio technology was proposed with the interference temperature constrain, in order to improve signal to interference plus noise ratio of CR. The problem of power control was changed into the problem of multi-restraints non-linear optimization with interference limits based on channel conditions, maximal network and power limits. The existence and unique of nash equilibrium (NE) in utility function by the principle of game theory and optimization were proved and a distributed algorithm for this game was proposed. Simulation results show that the proposed algorithm can improve users QoS (quality of serves), system performance effectively and improve radio resource efficiency.